1994
DOI: 10.1001/archpsyc.1994.03950100030003
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cerebrospinal Fluid Levels of Oxytocin in Obsessive-compulsive Disorder

Abstract: A possible role for oxytocin in the neurobiology of a subtype of OCD is suggested by the elevated CSF levels of oxytocin and by the correlation between CSF oxytocin levels and OCD severity. These findings reinforce the value of family genetic data in identifying biologically homogeneous (and perhaps more etiologically homogeneous) groups of patients with OCD. Together with emerging pharmacological data showing differential responsiveness to treatment of tic-related OCD vs non-tic-related OCD, these data also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(92 citation statements)
references
References 64 publications
4
87
0
1
Order By: Relevance
“…A range of symptomatology found in OCD patients, example, those related to contamination obsessions and washing, and those not related to tics, is congruent with a number of behavioral effects seen after the central administration of OT in animal models. 76 Leckman et al 24 had not only observed increase of OT levels in the CSF of patients with OCD without tics, but also a significant correlation between the concentrations of OT and the severity of the obsessive-compulsive symptoms. Moreover, OCD includes cognitive and behavioral symptoms similar to those induced through a central injection of OT in animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of symptomatology found in OCD patients, example, those related to contamination obsessions and washing, and those not related to tics, is congruent with a number of behavioral effects seen after the central administration of OT in animal models. 76 Leckman et al 24 had not only observed increase of OT levels in the CSF of patients with OCD without tics, but also a significant correlation between the concentrations of OT and the severity of the obsessive-compulsive symptoms. Moreover, OCD includes cognitive and behavioral symptoms similar to those induced through a central injection of OT in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although Leckman et al 24 have suggested a participation of OT in the pathophysiology of OCD, since high levels of this neuropeptide were found in the cerebrospinal fluid (CSF) of patients with OCD without tics, Altemus et al 25 found no differences in CSF levels of OT when OCD patients were compared with control subjects. The latter research group does not discard that central circuits might be responsible for these result differences.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear that these exogenous elevations of OT are related to differences in endogenous OT described here. There are several reports relating CSF and plasma levels of OT to human psychopathologies including OCD (Leckman et al, 1994), anorexia and depression (Frank et al, 2000), and Prader Willi syndrome (Martin et al, 1998). Differing basal levels and modulation of plasma OT levels have also been associated with differing levels of emotionality (Turner et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated oxytocin levels have been found in patients with non-tic-related obsessive-compulsive disorder (OCD) (Leckman et al, 1994), in children and adolescents with OCD and in Prader-Willi syndrome (Martin et al, 1998), a disorder with a high risk for comorbid OCD. One recent study was unable to confirm these results (Altemus et al, 1999); however unlike the Leckman study, this study did not separate patients with tics, or a family history of tics from those without tics.…”
Section: Introductionmentioning
confidence: 99%